Facebook viipurilaisten muistin paikkana - Hyyryläinen, Pirja (Viipurin Suomalainen Kirjallisuusseura, 2021)
The text looks at displaced Karelian groups – especially those related to Vyborg – on Facebook, which create a digital bridge between the past and the present. The groups are meta-archives as they store Vyborg-themed images and texts, share memories and host discussions related to Vyborg. There are participants from different generations. Facebook also enables virtual home region travel. peerReviewed